Representações sociais de jovens sobre trabalho: uma análise construída a partir da formação profissionalizante e da experiência de primeiro emprego - Betetto, Mariana de Freitas (2012)
The literature shows that the admission of young people in work force has positive and negative effects to his / her development. Given the current employment crisis and the legislation that foresees their inclusion in work as apprentices, it is important to analyze the social representations of young people whose admission in work force is mediated by preprofessional organizations, which should mediate the relationship between the apprentice and his first job experience, assuring him / her a temporary opportunity of qualification and labor. The goal of the research was to understand the social representations of the job among young people from 14 to 18 years old inserted as apprentices in a health insurance company located inwards Sao Paulo state. It was used the theoretical-methodological reference of the Social Representations Theory aiming to analyze how the social, historical and organizational effects of this type of insertion contributes to creating perceptions in youth about the job reality. It's about a case study involving the pre-professional entity, the health insurance company and the participation of 10 young apprentices from 16 to 17 years old, all students of High School in public schools of the city where the institutions that participates of the research are located. The social representations were collected by individual and group interviews, participant observation and bibliographic and documentary investigation. The data were analyzed by the construction of analytical categories a posteriori, that come from exhaustive and repeated readings of the results of interviews and records of field observations. Regarding the preprofessional organization, it was found that the type of qualification offered is disciplining and meets the capacity of the standard worker who is obedient and little flexible. The triangulation of information identified that young people represent the work ambiguously, showing positive and negative effects. The apprentices consider youth a period of preparation for work and very important for the professional future. The main advantages of the work pointed by them were: the provision for himself and family, the possibility of social mobility, the social contribution of labor (helping people), acquisition of responsibility and experience, support for school (guides the career choice), professional skills acquisition. Young people also showed the negative face of the job pointing, mainly, the lack of time to perform other activities such as study, leisure, living with relatives, among others. It was concluded that, from the apprentices' point of view, the job contributes more positively than negatively to their professional and personal development.